2017
DOI: 10.1111/1365-2664.12960
|View full text |Cite
|
Sign up to set email alerts
|

Mutualistic interactions amplify saltmarsh restoration success

Abstract: Mounting evidence shows that the functioning and stability of coastal ecosystems often depends critically on habitat‐forming foundation species such as seagrasses, mangroves and saltmarsh grasses that engage in facultative mutualistic interactions. However, although restoration science is now gradually expanding its long‐standing paradigm of minimizing competition to including intraspecific, or within species, facilitation in its designs, the potential of harnessing mutualistic interactions between species for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
74
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 75 publications
(80 citation statements)
references
References 53 publications
2
74
1
Order By: Relevance
“…Recent studies have shown that promoting positive interactions between individuals of the same species can increase restoration success (de Paoli et al, 2017; Silliman et al, 2015; van der Heide et al, 2007), highlighting the importance of facilitative interactions in restoring ecosystem‐engineering species (Maxwell et al, 2017). Facilitative interactions between ecosystem engineers may be equally important for promoting resilience and recovery (Angelini et al, 2016; Derksen‐Hoojiberg et al, 2018; Renzi, He, & Silliman, 2019; van de Koppel et al, 2015), but <3% of restoration projects have integrated interspecific interactions (Zhang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that promoting positive interactions between individuals of the same species can increase restoration success (de Paoli et al, 2017; Silliman et al, 2015; van der Heide et al, 2007), highlighting the importance of facilitative interactions in restoring ecosystem‐engineering species (Maxwell et al, 2017). Facilitative interactions between ecosystem engineers may be equally important for promoting resilience and recovery (Angelini et al, 2016; Derksen‐Hoojiberg et al, 2018; Renzi, He, & Silliman, 2019; van de Koppel et al, 2015), but <3% of restoration projects have integrated interspecific interactions (Zhang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Despite this investment, the majority of restoration projects either fail completely (Cunha et al, 2012;Tanner & Parham, 2010) or result in only partial recovery of the ecosystem (Rey Benayas, Newton, Diaz, & Bullock, 2009;Suding, 2011). This could be due to poor restoration designs and justifies the need to re-consider planting strategies (Derksen-Hooijberg et al, 2017;Silliman et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…, Derksen‐Hooijberg et al. ). Our study underlines these previous findings, but also calls for an extension of this framework: Rather than harnessing positive interactions, efforts to restore target species in ecosystems dominated by unwanted habitat‐modifying species should be aimed at breaking these self‐facilitative feedback mechanisms.…”
Section: Discussionmentioning
confidence: 99%